The Effect of Dividend Policy and Price Earning Ratio on Stock Returns - Bella Septawati; Rizki Yuli Sari (CAKRAWALA : Management Science Journal, 2024)
According to this study, companies listed on the Indonesia Stock  Exchange in the property and real estate industry from 2018 to 2022 will be influenced by the Dividend Policy (DPR) and Price Earnings Ratio (PER) on their stock returns. The purpose of this study is to empirically prove the effect of dividend policy proxied by Dividend Payout Ratio (DPR) and Price Earning Ratio on stock returns in  Property companies listed on the IDX for the 2019-2021 period. This research data comes from various sources, including company financial records and annual reports. The official website of the Indonesia Stock Exchange was consulted to obtain financial information and annual reports. The population of this study is companies listed on the Indonesia Stock Exchange in the property and real estate sector from 2018 to 2022. Six different organizations were selected for this study using purposive sampling. Sample data was obtained as many as 30 points for 5 years. the method used in this study is to use descriptive quantitative method research using multiple Linear Regression Analysis and Moderated Regression Analysis (MRA) from the SPSS 22 program. The results in this study are that dividend policy as measured using the Dividend Payout Ratio (DPR) does not affect the stock returns of companies in the property and real estate sector during the 2018-2022 period.